Chemical synthesis of peptides and peptide libraries - Hruby, Victor (Henry Stewart Talks, 2008)
Peptide and protein synthesis is the most robust of all synthetic chemistries, Very large combinatorial libraries with billions of different peptides are possible, Highly constrained peptides with specific secondary (phi/psi space) and tertiary (chi space) structures can be designed and synthesized, Peptides stable to proteolytic degradation and able to cross BBB can be synthesized, Peptides designed and synthesized with potent and selective bioactivities, Many excellent drugs, Peptide synthesis a critical tool for all aspects of chemical biology
Updated at 2022/08/24